The Effect of Affective Commitment and Work Motivation on Employee Performance at PT. Asrindo Citraseni Satria Minas - Hafizah, Yolanda; Fitri, Kurniawaty; Siregar, Prima Andreas (West Science Business and Management, 2026)
This study aims to analyze the influence of affective commitment and work motivation on employee performance at PT. Asrindo Citraseni Satria Minas. This study uses a quantitative approach with a questionnaire distribution method. The population in this study were office employees at PT. Asrindo Citraseni Satria Minas, with a sampling technique using saturated samples. Data were analyzed using multiple linear regression tests with the help of SPSS 25. The results showed that commitment has a negative and insignificant effect on employee performance. In addition, work motivation has a positive and significant effect on employee performance. Simultaneously, affective commitment and work motivation together have a significant effect on employee performance.